Doctor Zhivago - Campiotti, Giacomo, 1957-; Knightley, Keira, 1985-; Matheson, Hans, 1975- (Granada Television, 2002)
Δράμα εποχής με ήρωες δύο νέους που παλεύουν να κρατήσουν τον έρωτά τους ζωντανό μέσα στη δίνη του εμφύλιου σπαραγμού.